Personal growth in early pregnancy: the role of perceived stress and emotion regulation. (2nd November 2022) - Taubman–Ben-Ari, Orit; Chasson, Miriam; Horowitz, Eran; Azuri, Joseph; Davidi, Ofer
ABSTRACT: Objective: Coping with the stress aroused by early pregnancy can not only result in distress, but may constitute an opportunity to experience personal growth. Relying on the model of posttraumatic growth, this study examined the contribution of perceived stress and emotion regulation to women's personal growth during the first trimester of pregnancy. Method: A convenience sample of Israeli women (n=170), who were during their first trimester of pregnancy (up to 13 weeks), over 18 years old, and capable to completing the instruments in Hebrew, were recruited through a women's health clinic and through social media during the years 2017-2019. Results: The findings indicate that primiparous mothers report higher personal growth than multiparous. In addition, younger age, being primiparous, and higher cognitive-reappraisal contributed to greater personal growth. Moreover, a curvilinear association was found between perceived stress and personal growth, so that a medium level of stress was associated with the highest level of growth. Finally, cognitive-reappraisal fully mediated the relationship between perceived stress and personal growth. Conclusions: The findings add to the growing body of knowledge concerning the implications of early pregnancy in general, and personal growth as a result of dealing with the stress typical of this period in particular and highlight the role of the perceived stress as well as the woman's personal characteristics and resources that contribute to this result.